KAIDAH "AL-'ADAH MUHAKKAMAH" DALAM TRADISI PERNIKAHAN MASYARAKAT JAWA (Ahkam: Jurnal Hukum Islam, 2017)
Javanese people have many traditional ceremonies. Those ceremonies include the entire cycle of human lives; in the womb, birth, childhood, adolescence, marriage to death. One of the uniqueceremonies is the wedding ceremonies namely nontoni, lamaran, upacara tarub, and panggih. This research aims to describe kaeda of “Al-'Adah Muhakkamah” and its application on the marriage traditions of Javanese society. The study begins by explaining the meaning of kaeda, and finally explaining its application on the marriage traditions of Javanese society. The approach used in this research is descriptive-qualitative approach, because this study is intended to reveal and describe the kaeda and its application on those traditions. By using research methods outlined above, it can be concluded that based on that kaeda, the marriage traditions of Javanese society are allowed in Islam, and even can be used as excuses to establish law with the condition: they have been running for a long time and have known to the general public, they are accepted by common sense as good traditions, and they are not contrary to the Qur'anic texts and Hadith of the Prophet.Keywords: Al-'Adah Muhakkamah; Javanese society; Wedding Tradition.